Factors Influencing Success in Implementing Basic Floor Gymnastics Movement Learning Phase B - Shafa Nisrina; Agus Darmawan (Universitas Negeri Semarang, 2026)
Floor gymnastics learning at the elementary school level is an essential component of physical education that supports students’ motor development. This study aims to analyze the factors influencing the successful implementation of basic floor gymnastics movement learning among Phase B students at SD Negeri Adipala 07. This research used a descriptive quantitative approach with a questionnaire instrument consisting of 15 items distributed to third- and fourth-grade students, supported by direct observation during the learning process. The data were analyzed using descriptive percentage techniques with the assistance of Microsoft Excel 2019. The results showed that in grade III, internal factors obtained a percentage of 58% and external factors 68%, while in grade IV, internal factors obtained 57% and external factors 74%. All indicators were categorized as good. These findings indicate that external factors, including the teacher’s role, learning methods, facilities and infrastructure, and the learning environment, have a more dominant influence on learning success than students’ internal factors. This study concludes that the success of basic floor gymnastics learning requires synergy between student readiness, adaptive teacher competence, innovative learning methods, and adequate facility support.